Innovation platform of integrated transportation big data application technology - Xiaobo LIU; Yangsheng JIANG; Youhua TANG (大数据, 2018)
The integrated transportation systems in China are posing key issues such as insufficient service capability for trans-industrial and trans-regional transportation management.To deal with these issues,the construction goal of an innovative“Internet + Environment” platform that uses big data and artificial intelligent technologies to improve the system performance was proposed.The overall technological framework,research and development system,and the construction progress of the platform were introduced.